Unveiling the future: Smart airports - applications, advantages, strategies and technological challenges - Clara Dias; Jorge Silva (Journal of Airline and Airport Management, 2024)
Purpose: This paper aims to provide an insight onto the smart airport concept, its advantages and disadvantages as the world is constantly in a state of change. Concepts related to such revolution as well as its characteristics are increasingly being considered into various daily operations. As of so the concept of a Smart City has risen and with it the concept of a Smart Airport. These airports use these technologies to ease travelling processes and ensure safe and secure airports as well. Some of these are computerized check-ins and baggage tracks, smart screening, live tracking of passengers, and parking. Such changes in the aviation industry brought about by the fourth industrial revolution, guarantee that a number of airports will continue to grow.